The main peculiarities of labour migrants’ integration in Georgia (case of Tbilisi and Batumi) - Gogsadze, Giorgi (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2022)
Following the dissolution of the Soviet Union, Georgia became a country of intensive emigration. However, the last decade has marked a notable change in the country’s migration profile due to the inflow of immigrants. This is a new challenge for contemporary Georgia, especially in terms of immigrant integration. The purpose of this paper is to identify the main features of labour migrants’ integration into Georgian society. The research findings are mostly based on the results of a qualitative sociological research, employing indepth interviews with migrant workers residing in Georgia, and experts of the field. Lack of complete legislation and sound policies is the main characteristic feature of labour immigration management in Georgia; therefore, the migrant integration process goes spontaneously: one group of migrants, namely English- and Russian-speakers, as well as skilled workers still feel comfortable, and they keep intense communication with the local population. Another part of migrants who is denied state support in studying Georgian remains isolated from the host society.
Keywords: delovne migracije; demogeografija; Georgia; Gruzija; imigracija; labour migration; migracije; migration; population geography